THE ROLE OF MODERN COMPUTER TECHNOLOGIES (Modern education and development, 2025)
Computer engineering has seen rapid advancements in the past few decades, driven by the emergence of modern technologies. These innovations have revolutionized how we design, develop, and implement computer systems. This paper explores the latest technological trends in computer engineering, including artificial intelligence (AI), machine learning, quantum computing, the Internet of Things (IoT), and blockchain technology. It discusses their applications, impact on industries, and potential future developments. The integration of these technologies has not only transformed hardware and software design but also opened new possibilities for automation, data processing, and secure communication. The paper also delves into the challenges and ethical considerations that come with the adoption of these technologies.